THE EVOLUTION OF CYBERCRIME LEGISLATION - Chimchiuri, Lika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is analyzes the evolution of cybercrime legislation in several jurisdictions, with a focus on how laws are changing to reflect the complexities of cyber threats in a linked digital landscape. Research methods: this study uses a comparative analysis to identify major legislative developments across North America, Europe, Asia, and the rest of the developing world. Results: the fast development of digital technology has fueled the growth of cybercrimes such as hacking, phishing, and online fraud, posing new problems to judicial systems around the world. The study identifies comparable legislative frameworks, such as criminalizing unauthorized access to computer systems, as well as variations in approaches to penalties, jurisdiction, and enforcement roles. The paper goes further into the effectiveness of these laws in discouraging cybercrime, the difficulty of cross-border enforcement, and the delicate balance between crime prevention and individual privacy rights. Discussion: the article is to provide insights into the creation of strong legal frameworks that can keep up with the ever-changing nature of cyber risks by highlighting new trends and best practices. This analysis not only throws light on present legislative measures but also explores the implications for future policymaking in cybercrime prevention and punishment.